Harnessing Natural Language Processing (NLP) to Enhance Search Engine Performance - S K Sathya Hari Prasad; M Lavan (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
In the digital era characterized by an abundance of online information, efficient search engine tools are pivotal for navigating this vast ocean of content. Natural Language Processing (NLP), an offshoot of Artificial Intelligence, has emerged as a transformative force revolutionizing search engine, ensuring greater accuracy and efficacy in delivering search results. By Empowering Search Engines with NLP: NLP goes beyond the conventional keyword matching technique to unravel the genuine intent behind user queries, even when they are ambiguous or contain typos. Picture searching for the "best pizza near me" and receiving customized results tailored to your specific preferences, encompassing crust type, toppings, and individual dietary restrictions. Thanks to NLP, this is now within reach as it extracts the latent meaning concealed within apparently straightforward queries.